The interplay of real earnings management and investment efficiency: Evidence from the U.S. - Nedal Assad; Aziz Jaafar; Panagiotis D. Zervopoulos (Cogent Business & Management, 2023)
The main objective of this study is to empirically examine the impact of REM on various aspects of investment efficiency, including overinvestment and underinvestment. By examining the interplay between these complex constructs, this research endeavors to provide deeper insights and contribute to a more comprehensive understanding of the intricate effects of real earnings management on investment efficiency. This study utilizes a sample of 11,172 firm-year observations from publicly listed companies domiciled in the U.S. The study employs two empirical techniques to examine the research hypotheses: the generalized method of moments (GMM) and multinomial logit with two-way dimensional clustering. By employing robust analytical techniques, this research contributes to the scholarly discourse surrounding REM and its effect in shaping present and future investment. The results demonstrate a robust negative relationship between these two variables. Specifically, a negative association exists between a controlled or low-level of real earnings management with underinvestment and overinvestment. These findings imply that REM is a critical determinant of investment efficiency. Therefore, reducing REM can enable firms to optimize their investments more effectively.
Keywords: 650; agency theory; investment efficiency; overinvestment; real earnings management; underinvestment